Comparison of the Effectiveness of Jackfruit Banana Peel Extract, Kepok Banana Peel and Uli Banana Peel on Reducing Uric Acid Levels - Najwa Rokhmah, Nisa; Herlina, Nina; Andhika Riyantama, Alfi (JSMARTech, 2025)
This study aimed to compare the anti-hyperuricemia effects of ethanolic extracts from the peels of nangka, kepok, and uli bananas in male Sprague Dawley rats. Twenty-five rats (5–7 weeks old; 150–200 g) were randomly divided into five groups (n = 5 per group): a negative control (0.5% CMC-Na), a positive control (allopurinol 2.52 mg/200 g BW), and three treatment groups receiving 70 mg/200 g BW of each banana peel extract. The banana peels were extracted using the Ultrasound-Assisted Extraction (UAE) method with 70% ethanol. Hyperuricemia was induced for 10 days by oral administration of chicken liver juice (2 ml/kg body weight) for nine consecutive days, followed by a single intraperitoneal injection of potassium oxonate (50 mg/kg body weight) on the tenth day. Uric acid levels were measured using the uricase-PAP method and quantified with a microplate reader at 570 nm. Blood samples were collected from the tail vein and analyzed to determine uric acid concentration before and after treatment. Data were analyzed using a randomized block design (RBD), followed by ANOVA and Duncan’s post hoc test (α ≤ 0.05). The kepok banana peel extract showed the highest uric acid reduction (93.60%), followed by nangka (90.21%) and uli (81.26%). These results suggest that all three banana peel extracts possess significant anti-hyperuricemic activity, with kepok peel extract demonstrating the greatest potential for uric acid reduction. Keywords: Jackfruit Peel Extract, Cavendish Banana Peel Extract, Plantain Peel Extract, Anti-Hyperuricemia, Uric Acid